In-silico mining and characterization of MYB family genes in wilt-resistant hybrid guava (Psidium guajava × Psidium molle) - Ahmad, Israr; Soni, Sumit K.; M., Muthukumar; Pandey, Devendra (Journal of Genetic Engineering and Biotechnology, 2023)
Background The MYB family is one of the most significant groups of transcription factors in plants. However, several MYBs have been linked to secondary metabolism and are important for determining the color of fruit’s peel and pulp. Despite being a substantial fruit crop in tropical and subtropical areas of the world, wilt-resistant hybrid guava ( Psidium guajava × Psidium molle ; PGPM) has not yet been the subject of a thorough examination. This study’s goal was to assess the expression of MYB in guava fruit pulp, roots, and seeds to predict its function by in silico analysis of the guava root transcriptome data. Results In the current study, we have mined the MYBs family of MYB genes from the transcriptome of the PGPM guava root. We have mined 15 distinct MYB transcription factor genes/transcripts viz MYB3 , MYB4 , MYB23 , MYB86 , MYB90 , MYB308 , MYB5 , MYB82 , MYB114 , MYB6 , MYB305 , MYB44 , MYB51 , MYB46 , and MYB330 . From the analyses, it was found that R2-MYB and R3-MYB domains are conserved in all known guava MYB proteins. The expression of six different MYB TFs was examined using semi-quantitative RT-PCR in “Shweta” pulp (white colour pulp), “Lalit” pulp (red color pulp), “Lalit” root, and “Lalit” seed. Conclusion There were 15 MYB family members observed in guava. They were unequally distributed across the chromosomes, most likely as a result of gene duplication. Additionally, the expression patterns of the particular MYBs showed that MYB may be involved in the control of wilt, fruit ripening, seed development, and root development. Our results allow for a more thorough functional characterization of the guava MYB family genes and open the door to additional research into one essential MYB transcription factor family of genes and its involvement in the growth and ripening of guava fruit.